2019
DOI: 10.1016/j.heliyon.2019.e02414
|View full text |Cite|
|
Sign up to set email alerts
|

Studies on solvent precipitation of levan synthesized using Bacillus subtilis MTCC 441

Abstract: Levan is a water soluble biopolymer widely used in food, pharma, personal care and aquaculture industries. In this work, levan was synthesized by Bacillus subtilis MTCC 441 using sucrose as a sole carbon source. Effects of pH, sucrose concentration, nitrogen source, nitrogen concentration, inoculum size and agitation speed on levan production were studied. Yeast extract (YE) was found to be the best nitrogen source. Sucrose concentration – 100 g/L, pH – 7, YE concentration – 2 g/L, inoculum size 10% (v/v) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Contrary to the current study, Qaysi et al [ 31 ] reported that P. agglomerans ZMR7 produced the highest amount of levan after 96 h of incubation. Chidambaram et al [ 32 ] reported that the highest levan production was observed by using Bacillus subtilis MTCC 441, with 20 h of incubation, and using sucrose as the sole carbon source. Shih et al [ 33 ] reported that the highest levan production from Bacillus subtilis , under optimal conditions, was observed after 48 h of incubation with 250 g/L of available sucrose.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the current study, Qaysi et al [ 31 ] reported that P. agglomerans ZMR7 produced the highest amount of levan after 96 h of incubation. Chidambaram et al [ 32 ] reported that the highest levan production was observed by using Bacillus subtilis MTCC 441, with 20 h of incubation, and using sucrose as the sole carbon source. Shih et al [ 33 ] reported that the highest levan production from Bacillus subtilis , under optimal conditions, was observed after 48 h of incubation with 250 g/L of available sucrose.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal sucrose concentration for achieving maximum synthesis efficiency varies not only among different species but also often among different strains of microorganisms [ 19 , 20 ]. In the literature, there are various reports that indicate the capacity of some microorganisms to produce levan using sucrose as the only carbon source; among these, we can highlight Bacillus subtilis [ 21 , 22 ], Lactobacillus reuteri [ 23 ], and Leuconostoc citreum [ 24 ] and Gram-negative bacteria such as Gluconobacter albidus [ 25 ], Brenneria goodwinii [ 26 ], Erwinia tasmaniensis [ 27 ], and Halomonas smyrnensis [ 28 ]. Likewise, there are reports of the overexpression of the enzymes responsible for levan production; an example is the expression of the genes of Rahnella aquatilis [ 29 ] and Leuconostoc mesenteroides in Saccharomyces cerevisiae [ 30 ] and the genes of B. subtilis expressed in Pichia pastoris [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are reports that demonstrate that agro-industrial byproducts such as beet molasses, sugar cane molasses, and syrup have been used as alternative carbon sources and have allowed for adequate microbial growth and EPS production via SmF [ 26 , 41 ]. Levan is an EPS with a high potential to be used in various industries given its physicochemical and functional characteristics [ 24 , 42 ]; however, to improve performance and quality, the design of a process allowing for large-scale, efficient, ecological, and profitable production is necessary [ 7 , 21 ]. Because of this, the objective of the present work was to evaluate the EPS production potential of the indigenous yeast strain Suhomyces kilbournensis under different process conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Levan has a cationic property in an aqueous solution due to carboxyl and hydroxyl groups of its constituent substance fructose, contributing to its very stable shape. Levan is a functional material that is used in various industries such as functional cosmetics, agriculture, and industry because it is a water-soluble fructose polymer that melts not only at high temperatures, but also at low temperatures [ 28 , 29 , 30 ]. Therefore, levan-encapsulated enzymes or proteins have been studied and utilized to solve problems of reduced activities of proteinaceous substances such as enzymes.…”
Section: Introductionmentioning
confidence: 99%